THE USE OF GAMIFICATION TO IMPROVE STUDENTS' VOCABULARY MASTERY - Fiqih P, Emier Abdul (2017)
The research describes the use of gamification to improve students' vocabulary mastery. The research was aimed at discovering the use of gamification in helping junior high school students to improve their vocabulary mastery and the students' responses to the use of gamification to improve students' vocabulary mastery. Gamification in this research was the implementation of elements of game, namely: points, levels, leaderboard, avatar and challenge in mastering vocabulary. A classroom action research was employed as a research design in this research and it was divided into four phases namely Planning, Acting, Assessing, and Reflecting (as adapted from Kemmis & McTaggart, 1992). The data were collected through several instruments namely: classroom observation, students' assessment, and questionnaire, the data then analyzed by using the theory of qualitative data analysis proposed by Hamied and Malik (2016) while the mean score of the students' tests/assessments were calculated by using frequency distribution suggested by Hasan (2001). The result of the research revealed that the use of gamification has successfully improved students' vocabulary mastery which can be seen from the mean scores of pre-test, post-test in the end of cycle I, and post-test (from 52.87, 69.09, and 87.87). There were some students' responses regarding to the use of gamification such as: the students were motivated to learn new vocabulary with gamification.----------Skripsi ini mendeskripsikan tentang penggunaan gratifikasi untuk meningkatkan penguasaan vocabulary siswa. Skripsi ini bertujuan untuk mengetahui bagaimana penggunaan gratifikasi dalam membantu siswa Sekolah Menengah Pertama untuk meningkatkan penguasaan vocabulary siswa dan respons siswa terhadap penggunaan gratifikasi untuk meningkatkan penguasaan vocabulary. Gamifikasi dalam skripsi ini adalah pengimplementasian elemen-elemen permainan yang diantaranya: poin, level, klasemen, avatar, dan tantangan dalam menguasai vocabulary. Pada skripsi ini, PTK digunakan sebagai desain skripsi yang dibagi ke dalam empat tahap diantaranya Perencanaan, Pelaksanaan, Penilaian dan Refleksi (yang diadopsi dari Kemmis & McTaggart, 1992). Data yang diperoleh berdasarkan beberapa instrumen diantaranya: observasi kelas, tugas siswa dan kuesioner, lalu data dianalisis menggunakan teori analisis data kualitatif yang dikemukakan oleh Hamied and Malik (2016) yang rata-rata nilai tugas siswa dikalkulasikan menggunakan distribusi frekuensi yang dikemukakan oleh Hasan (2001). Hasil dari skripsi ini menunjukkan bahwa penggunaan gratifikasi secara sukses meningkatkan penguasaan vocabulary siswa yang bisa dilihat dari nilai rata-rata di pre-test, Post-test di akhir siklus pertama dan Post-test akhir (dari 52.87, 69.09, dan 87.87). Adapula beberapa respon siswa terkait penggunaan gratifikasi seperti siswa lebih termotivasi untuk mempelajari vocabulary baru menggunakan gratifikasi.